Pelatihan Sitasi Karya Ilmiah Menggunakan Mendeley - Faharuddin Situju, Sulfayanti; Nahya Nur; Hamrul, Heliawaty; Rasjid, Nurdina; Dian Megah Sari (Politeknik Negeri Cilacap, 2024)
Writing of scientific paper is done by following specified rules and regulations. In reality there are many students at the Faculty of Engineering, University of Sulawesi Barat who do not understand this well, for example: not paraphrasing quotations and not including reference sources correctly. Mendeley application can help students in writing scientific papers or final assignments but it still underutilized by students. This shows the importance of reference citing skills and utilizing the Mendeley application. So, it is necessary to conduct scientific paper citation training. The training was done through planning, training and evaluation activities. Planning aims to prepare and determine the needs during the training. The main activity, training, was organized for two days using a webinar concept on the first day which focused on providing material for preparing scientific work references and a training concept on the second day which focused on practice using Mendeley and coaching research proposals. Last activity, an evaluation was carried out to measure the successfulness of the training and further plans related to similar activities. The results of the training activities showed the participation of 68 students on the first day and 36 students on the second day. The results of the survey showed 100% of students who participated in training felt the benefits of the training therefore they hoped similar activities could be held every year. Another evaluation result is that student supervision should be done in small groups, so the reception of material more effective regarding how to cite scientific papers.